Secure hybrid RF/VLC under statistical queuing constraints - Gomes da Silva, Isabella W. [UNESP] (2021)
This paper evaluates the effective capacity and maximum average arrival rate of a hybrid radio frequency (RF) and visible light communication (VLC) network in the presence of an eavesdropper. It is assumed that the data is first stored in a buffer prior to transmission. Thus, it is considered that the source operates under constraints of buffer overflow probabilities. We also consider that the data is transmitted over the RF and VLC links following a proposed multiplex scheme in which the buffer service rate is described in terms of the secrecy capacity and split with a certain allocation ratio. Moreover, the legitimate and eavesdropper users are assumed to have multihoming capabilities so that are able to receive data from both access points simultaneously. We formulate an integral-form and asymptotic expressions for the effective capacity and validate them via Monte Carlo simulations. From the numerical results, we show that combining RF and VLC and splitting the data among them can enhance the performance in terms of the buffer quality of service (QoS) constraints and secrecy requirements.